Pengaruh Beban Pajak Tangguhan Dan Perencanaan Pajak Terhadap Manajemen Laba - Sri Utami; Martinus Budiantara (AKUNTANSI 45, 2024)
The purpose of this research is empirically examine the effect of deferred tax expense and tax planning on earnings management. The data in this study uses financial report data from food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the period from 2020 to 2022. Financial report in this study were obtained from www.idx.co.id. The samples used in this study were 12 companies using purposive sampling. The analytical method used is multiple linear regression analysis. The results of this study indicate that deferred tax expense and tax planning have no effect on earnings management.